Analisis Perbandingan Potensi Kebangkrutan dengan Model Grover, Altman Z-Score, Springate dan Zmijewski Pada Perusahaan Real Estate dan Property di Bursa Efek Indonesia - Eka Wulandari; Indra Fauzi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine whether the results of predictions for bankruptcy of Real Estate and Property companies on the Indonesia Stock Exchange are different using the Grover, Altman Z-Score, Springate and Zmijewski models in 2017-2019 and to find out the most accurate prediction model. The sample used in this study were 20 Real Estate and Property companies listed on the Indonesia Stock Exchange. The sampling technique was determined by purposive sampling method. The type of data used is secondary data with data collection using documentation and literature study methods. The data analysis technique used is the Kruskal-Wallis H test and the level of accuracy test. The results of this study indicate a significant difference between the Grover, Altman Z-Score, Springate and Zmijewski models, using the Kruskal-Wallis H Test. Then, the most accurate predictive model in predicting the bankruptcy of Real Estate and Property companies is Grover with an accuracy of 99 %.